A microfluidic platform for characterizing the structure and rheology of biofilm streamers. Issue 20 (10th May 2022) - Savorana, Giovanni; Słomka, Jonasz; Stocker, Roman; Rusconi, Roberto; Secchi, Eleonora
Abstract : We present a microfluidic platform with isolated micropillars as nucleation sites for the reproducible formation of biofilm streamers, whose biochemical composition, morphology, and rheology can be systematically characterized in situ . Abstract : Biofilm formation is the most successful survival strategy for bacterial communities. In the biofilm lifestyle, bacteria embed themselves in a self-secreted matrix of extracellular polymeric substances (EPS), which acts as a shield against mechanical and chemical insults. When ambient flow is present, this viscoelastic scaffold can take a streamlined shape, forming biofilm filaments suspended in flow, called streamers. Streamers significantly disrupt the fluid flow by causing rapid clogging and affect transport in aquatic environments. Despite their relevance, the structural and rheological characterization of biofilm streamers is still at an early stage. In this work, we present a microfluidic platform that allows the reproducible growth of biofilm streamers in controlled physico-chemical conditions and the characterization of their biochemical composition, morphology, and rheology in situ . We employed isolated micropillars as nucleation sites for the growth of single biofilm streamers under the continuous flow of a diluted bacterial suspension. By combining fluorescent staining of the EPS components and epifluorescence microscopy, we were able to characterize the biochemical composition and morphology of the streamers. Additionally, we optimized a protocol to perform hydrodynamic stress tests in situ, by inducing controlled variations of the fluid shear stress exerted on the streamers by the flow. Thus, the reproducibility of the formation process and the testing protocol make it possible to perform several consistent experimental replicates that provide statistically significant information. By allowing the systematic investigation of the role of biochemical composition on the structure and rheology of streamers, this platform will advance our understanding of biofilm formation.